Functional mitral regurgitation: predictor for atrial substrate remodeling and poor ablation outcome in paroxysmal atrial fibrillation. Issue 30 (July 2016) - Qiao, Yu; Wu, Lingmin; Hou, Bingbo; Sun, Wei; Zheng, Lihui; Ding, Ligang; Chen, Gang; Zhang, Shu; Yao, Yan
Abstract : Abstract: Functional mitral regurgitation (FMR) is not uncommon in atrial fibrillation (AF) patients. We sought to investigate the association between FMR and atrial substrate remodeling as well as the ablation outcome in paroxysmal AF (PAF) patients. We retrospectively analyzed a prospectively enrolled cohort of 132 patients (age 55.1 ± 9.6 years, 75.8% male) with symptomatic PAF who underwent initial ablation in our institute. Functional mitral regurgitation was defined as regurgitation jet area to left atrium (LA) area ratio ≥ 0.1 without any primary valvular disease. Voltage mapping of LA was performed under sinus rhythm. Low voltage zones (LVZs) were semi-quantitatively estimated and presented as low voltage index. Follow-up for AF recurrence ≥ 12 months was performed. In total, 40 patients (29.6%) were detected with FMR, who were older than the non-FMR patients ( P  = 0.007) and had larger LA diameters ( P  = 0.02). Left atrium LVZs were observed in 64.9% of patients with FMR versus 22.1% patients without FMR ( P  < 0.001). Functional mitral regurgitation independently predicted the presence of LVZs (OR 7.286; 95% CI 3.023–17.562; P  < 0.001). During a mean follow-up of 22.9 ± 6.5 months, 38 patients (28.8%) experienced AF recurrence. The recurrence rate was 60.0% and 19.5% in FMR and non-FMR cohort, respectively (log rank P  < 0.001). Multivariate analysis showed that FMR was an independent predictor for AF recurrence (HR 2.291; 95% CI 1.062–4.942; P  = 0.03). Functional mitral regurgitation was strongly associated with atrial substrate remodeling. Furthermore, patients with FMR have substantial risk for AF recurrence post ablation. Abstract : Supplemental Digital Content is available in the text